ANALISIS RAGAM BAHASA DAN NILAI MORAL DALAM NOVEL “AYAH” KARYA ANDREA HIRATA - Floriano Andi Dtanjoeng; Ni Luh Sukanadi; Dewa Gede Bambang Erawan (JIPBSI (Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia), 2021)
The selection of the novel "Ayah" as a research material is based on the story in this novel which presents many interesting stories and life problems and there are various languages and moral values which are very useful for readers. This study aims to analyze the variety of languages and moral values contained in the novel "Ayah" by Andrea Hirata. The method used in this research is a qualitative approach. The results of this study found that the varieties of language contained in the novel "Ayah" by Andrea Hirata consisted of: literary, dialectic, functional, informal, scientific, oral, uneducated, and social varieties. The moral values contained in the novel "Ayah" by Andrea Hirata consist of: the value of care, the value of chastity, the value of sacrifice, the value of honesty, the value of politeness, the value of discipline, and the value of independence.